Biocentrism, Religion and Synthetic Biology - Attfield, Robin (Worldviews, 2013)
Biocentrism maintains that all living creatures have moral standing, but need not claim that all have equal moral significance. This moral standing extends to organisms generated through human interventions, whether by conventional breeding, genetic engineering, or synthetic biology. Our responsibilities with regard to future generations are relevant to non-human species as well as future human generations. Likewise, the Precautionary Principle raises objections to the generation of serious or irreversible harm or changes to the quality of human or non-human life, and needs to be applied when the introduction of synthetic biotechnology is envisaged. Consideration of this Principle supplements the problems raised for synthetic biology from a biocentric perspective. The bearing of biocentrism on religions is also considered, together with contrasting views about science, religion and the creation of life.